2022
DOI: 10.1155/2022/7276028
|View full text |Cite|
|
Sign up to set email alerts
|

An Approach for Cardiac Coronary Detection of Heart Signal Based on Harris Hawks Optimization and Multichannel Deep Convolutional Learning

Abstract: Automatic diagnosis of arrhythmia by electrocardiogram has a significant role to play in preventing and detecting cardiovascular disease at an early stage. In this study, a deep neural network model based on Harris hawks optimization is presented to arrive at a temporal and spatial fusion of information from ECG signals. Compared with the initial model of the multichannel deep neural network mechanism, the proposed model of this research has a flexible input length; the number of parameters is halved and it ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Therefore, many researchers in computer science have focused on the use of algorithms and various innovative techniques in developing systems specialized in detecting and diagnosing heart diseases. An electrocardiogram (ECG) signal is the most efficient and powerful tool for diagnosing heart disease and indicates the heart's electrical activity 1,2 . Among the difficulties faced in this study were the morphology of the ECG varies from person to person and its diversity, the effect of negative noise on ASHA, Medical errors in diagnosis that occurred as a result of lack of experience or work pressure and Low diagnostic accuracy in traditional diagnostic algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many researchers in computer science have focused on the use of algorithms and various innovative techniques in developing systems specialized in detecting and diagnosing heart diseases. An electrocardiogram (ECG) signal is the most efficient and powerful tool for diagnosing heart disease and indicates the heart's electrical activity 1,2 . Among the difficulties faced in this study were the morphology of the ECG varies from person to person and its diversity, the effect of negative noise on ASHA, Medical errors in diagnosis that occurred as a result of lack of experience or work pressure and Low diagnostic accuracy in traditional diagnostic algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%